The Role of Estrogen in the Development of Breast Cancer - Nikki Aldi Massardi (Biomedical Journal of Indonesia, 2021)
Breast cancer is a hormone-dependent disease that relies on the mitogenic effect of estrogen to increase tumorigenesis and tumor growth. Clinically significant levels of estrogen-α receptor (ERα) expression are seen in 80% of human breast cancers, whereas progesterone receptor is expressed in 55% of human breast cancers. These data are one of the bases for the development of endocrine therapy. Endocrine therapy is therapy that targets the pathway and synthesis of estrogen, by blocking it via receptors, reducing circulating levels of estrogen, or suppressing estrogen synthesis in the tissues of women diagnosed with breast cancer.